Faktor-faktor Penyebab Rendahnya Kinerja Pustakawan di Kantor Perpustakaan, Arsip, dan Dokumentasi (KPAD) Pesisir Selatan - Winarandu, Jeky; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
This study aims to (1) describe the factors that cause poor performance of the librarian in the Office of Library, Archives and Documentation (KPAD) South Coast. (2) Analyzing the Performance Improvement Effort In The Office Librarians Libraries, Archives and Documentation (KPAD) South Coast. This research is interviews and field observations. Based on these date, it was found that the results of the first study, the causes of the poor performance of the employees of the Office of Libraries, Archives and Documentation South Coast is in terms of personal skills, lack of discipline, and lack of human resources. Second, quality improvement procedures among employees working in the office section of the library libraries, archives, and documentation of the south coast, such as motivation, good leadership motivation coworkers, and family, as well as from the personal capability librarian. Third, the promotion to the general public. Keywords: performance; librarian